TRANSIENT ANALYSIS OF LUMPED PARAMETER RLC CIRCUIT FOR DIFFERENT DAMPING CASE USING ONE DIMENSIONAL TRANSMISSION LINE MODELING (TLM) METHOD - Kibria, M. F.; Danesh, Hajee Mohammad (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
Here, the transient analysis of lumped parameter RLC circuit is analyzed for different damping case using one dimensional TLM method. The circuit is modeled to derive the required algebraic iterative equation using stub model of the above mentioned method. The model equations using TLM method are arranged systematically so that those can be implemented easily to the existing MATLAB software for the purpose of analytical result. We considered the analytical result of the classical method using differential equations as the reference method for comparison. Finally, the analytical results using TLM method are compared with classical method for appraisal.